Nanotechnology safety in Asian perspective: A legal analysis - Karim, M.E. (2013)
Nanotechnology has the prospect to vibrate the imagination of human being and has the ability to be used in almost every sector of human need. With its limitless potential, there are concerns too as nanoparticles have been projected as next asbestos. Studies revealed that nanoparticles can enter the human body through the lungs, intestinal tract, and skin and can create serious problems and thus, the researchers and workers who remain the closest due to the nature of their job can be seriously affected. The incident of death and lungs damage of workers of the Chinese paint factory and the confirmation by the physicians compels to consider the issues of nanosafety very seriously. Different organizations at European level and America have been working to frame some Code, Guideline and Policy, etc. in this regard where Asia is still far behind. This paper aims at sharing the legal and regulatory set up of some of the Asian countries in relation to nanotechnology safety. Language being a problem in jotting down the resources on these countries, this paper will consider only the resources available online in English.